Paintings in the Oval Cartouches in the Ceiling - Temples of India Project Team (Jio Institute, 2024)
A closer view of the paintings in the oval cartouches in the ceiling of the mandapa (pillared hall) of the Bhandasar Temple. Seen here are many ovals depicting different stories. The lower set has stories of miracles of Jinadatta Suri, like saving a child’s life, procuring the sacred scriptures hidden inside a pillar, and capturing the lightning in his alms bowl. The upper circle has Jain monks and auspicious symbols for Jain tradition like Chaude Rajlok and Mokhs Parinirvana, enunciating the worldly life. The oval shapes of the paintings are designed like mirror frames. This style is influenced by European paintings, especially the Company style paintings produced during the 18th – 19th centuries CE.